Internationalizing Students in the Home Country- Dutch policies - Van Gaalen, Adinda; Gielesen, Renate (International Higher Education, 2014)
This article discusses how internationalization at home can be stimulated based on results of study of 54 Dutch higher education institutions. The article shows that although internationalization at home is one of the key elements of the internationalization agenda, implementation is challenged by a lack of attention to training of staff in this specific field.